Battery Protection System Against Undervoltage and Overvoltage in Off-Grid Systems Photovoltaic - Dwi Nur Fitriyanah; Nicken Ayu Febrianti Soeyoto; Imam Abadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Electrical energy at this time is widely used by most humans, of course also disturbances in the distribution of electricity cause inhibition of daily human activities. Disturbances that occur can be classified into various kinds, one example is Undervoltage and overvoltage. Of course, these disturbances can arise when the use of electrical loads that are sensitive to damage. To secure electrical loads that are sensitive to damage, a control system is made overvoltage and undervoltage using a microcontroller Arduino Mega and the actuator is a relay. This research tries to solve the problem of over voltage, under voltage, and unbalanced voltage with a visual basic-based voltage protection system. This system research uses visual basic as an interface and as a data logger to facilitate operators in analyzing disturbances, and with the help of the Arduino Mega2560 microcontroller which can be used to process and send data to the visual base. Thus, this research is expected to help users to e easily monitor and analyze disturbances.